2017
DOI: 10.1136/bmjopen-2016-013700
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between preconception maternal non-occupational exposure to interior decoration or oil paint odour and average birth weight of neonates: findings from a nationwide cohort study in China’s rural areas

Abstract: BackgroundBirth weight is a critical indicator of neonatal health and foretells people’s health in adolescence and even adulthood. Some researchers have warned against the adverse effects on babies’ birth weight of exposure to pollutants in interior decoration or oil paint by odour intake. This study evaluated the effects of maternal exposure to such factors before conception on the birth weights of neonates.MethodsData on 213 461 cases in this study were from the database of the free National Pre-pregnancy Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…24,40 The cohort study of 213 461 births in China found that women who were exposed to interior decoration or oil paint odor at home or in the workplace within 6 months before their pregnancy had significantly lower incidence of LBW than other women without these exposures. 24,40 The cohort study of 213 461 births in China found that women who were exposed to interior decoration or oil paint odor at home or in the workplace within 6 months before their pregnancy had significantly lower incidence of LBW than other women without these exposures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…24,40 The cohort study of 213 461 births in China found that women who were exposed to interior decoration or oil paint odor at home or in the workplace within 6 months before their pregnancy had significantly lower incidence of LBW than other women without these exposures. 24,40 The cohort study of 213 461 births in China found that women who were exposed to interior decoration or oil paint odor at home or in the workplace within 6 months before their pregnancy had significantly lower incidence of LBW than other women without these exposures.…”
Section: Discussionmentioning
confidence: 99%
“…24,40 The cohort study of 213 461 births in China found that women who were exposed to interior decoration or oil paint odor at home or in the workplace within 6 months before their pregnancy had significantly lower incidence of LBW than other women without these exposures. Secondly, the definition of renovation-related exposure in the nationwide cohort study was interior decoration or oil paint odor at home or in the workplace within 6 months before their pregnancy, 24 whereas the corresponding definition in our study was household renovation during the year before pregnancy. We suspect that the differences between the studied associations are partly due to urban-rural differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations